THE ACTIVE LEARNING ATTRIBUTES AND EMPLOYABILITY READINESS AMONG ENGINEERING GRADUATES IN THE HIGH EDUCATION INSTITUTES IN OMAN - Al Hinai, Masoud Rashid; Bhuiyan, Abul Bashar; Husin, Nor Azilah (International Journal of Business and Management Future, 2021)
The aim of this study is to investigate the effects of Active Learning attributes on the employability readiness of the engineering graduates of the High Education Institutes in Oman. The study adopted self-directed structured questionnaire was distributed to a sample of engineering students and graduates from a number of colleges and universities. The study used the structural equation modelling (SEM) for analysed the collected data. The findings of the study reveal that universities active learning facilities have high positive attribution for promoting team work skills, learning in safe working environment, endorsing adaptability skills, and developing analytical thinking abilities among graduates. However, the findings of the study indicate that HEIs are requested to effectively utilise active learning facilities to promote the attainment of technical skills, development of lifelong learning skills especially the openness to new ideas and the drive to use new technologies, endorsement of problem-solving skills, and the engagement and the development of graduates’ intrinsic motivation to improve their graduates’ Readiness for Employability. Specifically, study findings showed Active Learning attributes factor could have high influence on the Readiness for Employability of the graduates in Oman when they are utilised effectively. Finally, the study’s implementations and recommendations could be transferred to the Gulf and Arab or other countries’ contexts having similar settings of HE systems and similar issues of skills gap and employability concern of their graduates.